Effect of cobalt isomorphic substitution on the properties of goethite and the adsorption of lead - Liu, Xu; Xue, Wenlu; Zhang, Zijia; Zhou, Wei; Song, Shaoxian; Li, Yinta; Benzaazoua, Mostafa; Hu, Xiheng (Frontiers in Environmental Science, 2023)
Iron oxides are ubiquitously in environment and often contain impurities because of the substitution by Al, Mn, Co and other metals. However, few studies focused on Co substitution and subsequent Pb(II) adsorption on its surfaces. Herein the effect of isomorphous substitution of Co on the physiochemical properties of goethite and the atomic-level mechanisms of lead sorption in relation to structural changes were investigated in this work. The results showed that Co-substitution reduced the unit cell parameters and crystallinity of goethite. More Fe-OH groups on the surface were exposed with Co substitution, leading the preferential sorption of Pb. The DFT calculation further revealed that the valence band was shortened and the total density of states was more biased towards the Fermi level in Co-substituted goethite, making the surface electrons more active. In addition, both Pb2+ and Pb(OH)+ were adsorbed by goethite through forming a tridentate complex with three oxygen atoms. In this process, sp3 hybridization mainly occurred. These results provide a new perspective for studying the properties of Co-goethite and its reaction with lead, helping expand the application of DFT calculations to simulate and predict the fixation and mobilization of heavy metals in goethite-rich soils/sediments.